Preconcentration and determination of metal ions in commercial ethanol used as fuel for automotive engines - Dias Filho, Newton Luiz [UNESP]; Costa, Reginaldo Mendonca [UNESP]; Okajima, Giovana Lopes [UNESP] (Taylor & Francis Inc, 2008)
The present investigation reports the synthesis, characterization, and adsorption properties of a new nanomaterial based on organomodified silsesquioxane nanocages. The adsorption isotherms for CuCl,, CoCl2, ZnCl2, NiCl2, and FeCl3 from ethanol solutions were performed by using the batchwise method. The equilibrium condition is reached very quickly (3 min), indicating that the adsorption sites are well exposed. The results obtained in the flow experiments, showed a recovery of ca. 100% of the metal ions adsorbed in a column packed with 2 g of the nanomaterial, using 5 mL of 1.0 mol L-1 HCl solution as eluent. The sorption-desorption of the metal ions made possible the development of a method for preconcentration and determination of metal ions at trace level in commercial ethanol, used as fuel for car engines. The values determined by recommended method for plants 1, 2, and 3 indicated an amount of copper of 51, 60, and 78 mu g L-1, and of iron of 2, 15, and 13 mu g L-1, respectively. These values are very close to those determined by conventional analytical methods. Thus, these similar values demonstrated the accuracy of the determination by recommended method.
Keywords: fuel ethanol; preconcentration; adsorption; isotherms of adsorption; transition-metal ions